REPRESENTING THE OTHER: LIMITS OF INTERRELIGIOUS DIALOGUE - C Canceran, Delfo (Asian Horizons, 2017)
This article tackles the problematic aspect of interreligious dialogue. Representation is not presentation because it takes place in language which cannot be contained or fixed. The primary reason is that the other is opaque and illusive. The alterity of the other remains ungraspable and undecidable. Thus, dialogue is always open to the unexpected wholly other that comes and surprises the self. This limit of representing the other does not paralyze the participants or actors in dialogue but challenges them to push and even break it.